A Novel Finite-Control-Set Model Predictive Torque Control for Five-Phase PMSM With Improved Harmonic Current Suppression - Weiguo Tao; Huawei Zhou; Chen Ye; Cheng Chen (IEEE Access)
There is the third harmonic current in five-phase permanent magnet synchronous motors (PMSMs), thus causing the distortion of stator currents and additional copper loss. Although the existing finite-control-set with virtual voltage vectors (FCS-V3s) can eliminate the harmonic voltage of harmonic subspace, it completely loses the ability to control the harmonic subspace. Moreover, the DC-link utilization is reduced due to the usage of V3s. To address these problems, a novel FCS model predictive torque control (FCS-MPTC) was proposed to be an alternative to the existing FCS-MPTC in this paper. First, a novel FCS was designed to achieve the double closed-loop control for both subspaces. Then, all the specific duty ratios were calculated and further limited to the normal range from the geometric point of view. Moreover, a wider amplitude range of available voltages was obtained in the novel FCS. Consequently, compared with the existing virtual-VVs-based FCS-MPTC (FCS-V3s-MPTC), the proposed method can effectively suppress the third harmonic current generated by the motor itself, improve the DC-link utilization while achieving the good steady-state and dynamic response performance. Finally, experimental results were presented to validate the effectiveness of proposed method.